Effects of a 6 week core strengthening training on measures of physical and athletic performance in adolescent male sub-elite handball players - Bauer, J.; Muehlbauer, T. (Frontiers in Sports and Active Living, 2022)
The objective was to investigate the effects of a 6-week core strengthening training within the regular handball training sessions compared to regular handball training only. Male sub-elite handball players were randomly assigned to an intervention (INT: n = 13; age: 16.9 ± 0.6 years) or a control (CON: n = 13; age: 17.2 ± 0.8 years) group. The INT group performed the "big 3" core exercises cross curls-up, side bridge (both sides), and the quadrupedal stance ("birddog exercise") triweekly for 20-30 min while the CON group conducted regular handball training only. Pre- and post-training assessments included measures of muscular endurance (Closed Kinetic Chain Upper Extremity Stability Test [CKCUEST] and the Bourban test), shoulder mobility/stability (Upper Quarter Y Balance [YBT-UQ] test), and throwing velocity. The ANCOVA revealed significant differences between means in favour of the INT group for the dorsal chain (p < 0.001, ?2p = 0.46) and the lateral chain (left side: p = 0.015, ?2p = 0.22; right side: p = 0.039, ?2p = 0.17) of the Bourban test, the composite score (p = 0.024, ?2p = 0.20) of the throwing arm reach and the inferolateral reach direction (p = 0.038, ?2p = 0.17), and the composite score (p = 0.027, ?2p = 0.19) of the non-throwing arm reach of the YBT-UQ. However, performance in the CKCUEST and throwing velocity did not show any group-specific changes. Therefore, 6 weeks of core strengthening training were effective in improving some components of physical but no handball-specific athletic (i.e., throwing velocity) performance in adolescent male sub-elite handball players. Practitioners may still opt for this training regimen when stimulus variability is sought or when a low load/low movement approach (e.g., during rehabilitation) is favoured.